Intrusion-related (ca. 422 Ma), monzogranite-hosted Au-Ag-Sb mineralization at the Yellow Fox zone, eastern Mount Peyton Intrusive Suite, north-central Newfoundland, Canada - Sandeman, Hamish A. I.; Honsberger, Ian W.; Spurrell, Cody; Peddle, Cameron; Dunning, Gregory; Camacho, Alfredo (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The northeastern and eastern parts of the ca. 425–416 Ma Mount Peyton Intrusive Suite in north-central Newfoundland, Canada, host several Au-Ag-Sb-bearing mineralized zones associated with fracture systems and narrow quartz veins mantled by wide, potassic (sericite-muscovite) alteration envelopes bearing arsenopyrite and locally pyrite and stibnite. The Yellow Fox zone is hosted in a medium-grained and plagioclase-porphyritic, granophyric-textured biotite ± hornblende I-type transitional to A2-type monzogranite in the northeastern part of the intrusive suite that is cut by rectilinearly fractured, muscovite-arsenopyrite-pyrite-rutile-alteration zones. This alteration occurs in an ~100 m long by 30 m wide, north-trending bleached and rusty alteration zone characterized by three distinct fracture sets: (1) a widely spaced, roughly east-west barren set; (2) a prominent north-trending 5–20 cm spaced set accompanied by abundant muscovite and disseminated arsenopyrite + pyrite; and (3) a weakly-developed, north-northeast-trending set that locally hosts a few narrow (<4 cm) stibnite-quartz-arsenopyrite veins with arsenopyrite mainly confined to the quartz vein margins and intensely altered to supergene scorodite and goethite. Relative to unaltered granite, both muscovite-pyrite-arsenopyrite-rutile-altered monzogranite and stibnite-quartz-arsenopyrite-veined monzogranite are anomalous in many metals (Sb <11.1 wt.%; As < 4.5 wt.%; Au <59.4 g/t; Ag < 73g/t; Pb <5.5 wt.%; Zn <7 wt.%; Cd <717 ppm). The altered host rock yielded a crystallization age of 422.3 ± 1.3 Ma (CA-ID-TIMS U–Pb zircon), overlapping in error with two 40Ar/39Ar incremental-heating ages of 422.4 ± 0.2 Ma and 422.9 ± 0.6 Ma for muscovite from the same altered monzogranite. The coincident ages indicate that monzogranite crystallization and alteration were synchronous and therefore intrusion-related and formed broadly contemporaneously with proximal, mineralogically similar, intrusion-hosted mineralization in the region. Undated Au-Ag-As-Sb mineralization in the adjacent surrounding country rocks may also have been coeval. Fracturing, release of hydrothermal + magmatic fluids from deeper seated intrusions, and mineralization occurred during the final stages of monzogranite crystallization, which is interpreted to be associated with transient lithospheric extension that preceded north- to northwest-directed oblique Acadian thrusting, folding, and proximal orogenic Au mineralization in the Early Devonian (ca. <415 Ma).